The Role of the Emotional Intelligence in the Development of in Dividual Leader Shipskills - Kasianova, Svitlana (Psychological Prospects Journal, 2018)
The article presents the empirical study results of the students’ emotional intelligence and leadership skills in socionomic professions (unemployed who undergo professional retraining). Interrelations are established and the possibility of their development is determined in the learning process. It was established that the majority of respondents have moderate or low development levels of emotional intelligence and leadership skills. They mostly possess information about the nature of the emotions and emotional states, can put themselves in the place of another and take into account in the decision-making process feelings and emotions of other people. However, they have lack of motivation, difficulties in managing their emotions, are not always self-critical and it is difficult for them to make their own decisions independently and in time.118–130 A holistic and systematic impact on the development of the emotional intelligence of the students was carried out through the course «Development of the emotional intelligence», the purpose of which was to acquire practical skills for understanding, managing their own emotions and emotions of other people. It was established that at the end of the study the scales were significantly increased in «Emotional Awareness», «Managing own emotions», «Self-motivation», «Empathy», «Integrative level of emotional intelligence», «Level of leadership skills».The statistical processing of the results confirmed the significant differences in the average scores of these scales. This made it possible to conclude that the students could develop them through special training sessions in the process of the professional retraining. All correlations are of a direct nature, so, the higher the emotional intelligence level of development, the more expressed are the leadership skills. The following components of emotional intelligence are most strongly influenced by the development of the leadership skills: «Managing own emotions», «Self-motivation», «Recognizing the emotions of other people», «Integrative emotional intelligence»(positive close relations are established).Research perspectives include the design and implementation of training programs for the development of emotional intelligence and leadership skills of the students (the unemployed) who would be successful in their employment.